Genomic and transcriptomic profiling of Coeliac Disease - Coleman, Ciara (Trinity College (Dublin, Ireland). Department of Genetics, 2016)
Coeliac Disease (CD) is a chronic immune mediated disease triggered by the ingestion of gluten. It has an estimated prevalence of approximately 1% in European populations. Genome-wide association studies (GWAS) have identified a large number of CD risk loci to date that have added substantially to our understanding of the genetic complexity of CD. However despite these major advancements, replication of such findings is scarce. Therefore replication of disease-associated loci in independent populations is considered to be a necessary validation step. This thesis set out to replicate findings from a recent large Immunochip analysis in an independent Irish case-control sample. We show that direction of effect of previously identified risk alleles highly correlated with those in the Irish population.
Keywords: Genetics, Ph.D.; PhD Trinity College Dublin, 2016